Secondary prevention of colorectal cancer - Dušičková, Tereza; Bártlová, Sylva (Jihočeská univerzita v Českých Budějovicích, Zdravotně sociální fakulta, 2019)
Goal: The goal of this review study is to map the options of secondary prevention of colorectal cancer.Methods: We used the method of document content analysis. We searched for references using the following keywords: “screening”, “colorectal cancer”, “occult bleeding”, “colonoscopy”, and the Boole operators “AND” and “NOT”. We used the databases of EBSCO, ProQuest and Pubmed between February and April 2019. After the filtering, we included 20 sources. Results: The study shows that if colorectal cancer is treated in the early phase, there is a higher probability of survival. We also confirmed a decreased incidence and mortality using the screening of risk groups. The colorectal carcinoma screening is carried out by testing the stool or colonoscopy. To test the stool, we can use haemoccult (gFOBT), immunochemical techniques (FIT) or DNA mutation testing in the stool. Conclusion: There is not a unanimous recommendation for colorectal carcinoma screening. Some countries have state regulations. This research shows that there is not sufficient proof for using haemoccult tests or immunochemical techniques.
Sekundární prevence kolorektálního karcinomu
Keywords: Colorectal tumor; Diagnostics; Nurse; Screening; Secondary prevention; kolorektální karcinom; diagnostika; sestra; screening; sekundární prevence